A study of the Causes of Schools Dropout in Andhra Pradesh - challabathula, Dr.subha kumar (IJRDO - Journal of Business Management, 2018)
Present study of Causes of school Dropout in Andhra Pradesh. Education is a basic need and right of every human being. It seeks to develop innate inner capacities of man. Education is the manifestation of the divine perfection, already existing in man (Vivekananda). Education gives knowledge of the word around us it develops in us a perspective of looking of life. It helps us build opinion and have point of view on things in life. Education is important as it teaches the right behavior and good manners, thus, makes civilized. It teaches how to lead life and organizational skills. It develops social skills for interacting with others. It is the basis of culture and civilization. The present research work is considered as an explanatory study aimed primary at going on insight the causes of schooling dropouts of Andhra Pradesh. Results of the study was the dropout rate at primary school in A.P in2013-14 was 4.35%, 2014-15 year was 6.72% and 2016-17 year dropout rate at primary school was 9.68. Main causes of school dropout are traditional thinking, failure, help demanded from them in household work and labour activities, lack of education among parents, lack of interest in subjects, inferiority among poor, backward families, etc.